Effect of Earlier Door-to-CT and Door-to-Bleeding Control in Severe Blunt Trauma: A Retrospective Cohort Study - Murao, Shuhei (J Clin Med, 2021)
Blunt trauma is a potentially life-threatening injury that requires prompt diagnostic examination and therapeutic intervention. Nevertheless, how impactful a rapid response time is on mortality or functional outcomes has not been well-investigated. This study aimed to evaluate effects of earlier door-to-computed tomography time (D2CT) and door-to-bleeding control time (D2BC) on clinical outcomes in severe blunt trauma. This was a single-center, retrospective cohort study of patients with severe blunt trauma (Injury Severity Score > 16). To assess the effect of earlier D2CT and D2BC on clinical outcomes, we conducted multivariable regression analyses with a consideration for nonlinear associations. Among 671 patients with severe blunt trauma who underwent CT scanning, 163 patients received an emergency bleeding control procedure. The median D2CT and D2BC were 19 min and 57 min, respectively. In a Cox proportional hazard regression model, earlier D2CT was not associated with improved 28-day mortality (p = 0.30), but it was significantly associated with decreased mortality from exsanguination (p = 0.003). Earlier D2BC was significantly associated with improved 28-day mortality (p = 0.026). In conclusion, earlier time to a hemostatic procedure was independently associated with decreased mortality. Meanwhile, time benefits of earlier CT examination were not observed for overall survival but were observed for decreased mortality from exsanguination.